Penyusunan Metodologi Perencanaan Strategis Sistem Informasi Berbasis Value Bisnis (Be Vissta Planning) untuk Meningkatkan Peran Strategis Sistem Informasi pada Suatu Organisasi (Bagian I) - Atmaja, Wahyu H. K. (Journal the Winners: Economics, Business, Management, and Information System Journal, 2002)
Objective of the research is to establish an Information System (IS) Strategic Planning Method based on business value that produces a blue print for system, technology, and information management. Method of the research was conducted by library research which was an analysis based on the compilation of available methods and IS strategic planning tools. The analysis was conducted on comparation of activities, tools, and documents which are used in the information system strategic planning methods. It is concluded that: 1) A logical flow of IS strategic planning can be obtained by comparing and arranging activities based on some strategic planning methods; 2) The comparation and arrangement of some IS strategic planning methods reflect similarities and differences that should be compiled to establish a logical frame of bussines value based information system strategic planning; 3) This logical frame of BVP adopts UK Government CCTA â€“ Guidelines on Strategic Planning for Information Systems in order to establish a more reliable and validÂ  IS strategic planning method.